Synthesis of Five-Membered Iodine–Nitrogen Heterocycles from Benzimidazole-Based Iodonium Salts; Journal of Organic Chemistry (JOC); Vol. 83, iss. 19 - Vlasenko Yu. A. Yuliya Aleksandrovna; Postnikov P. S. Pavel Sergeevich; Trusova M. E. Marina Evgenievna; Shafir A. Alexandr; Zhdankin V. V. Viktor Vladimirovich; Yoshimura A. Akira; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich) (2018, 2018)
Title screen